1991
DOI: 10.1073/pnas.88.18.8003
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional ordering of the DNA base guanine observed by scanning tunneling microscopy.

Abstract: Guanine, one ofthe four DNA bases, has been observed by tunneling microscopy to form a two-dimensional ordered structure on two crystalline substrates, graphite and MoS2. The two-dimensional lattice formed by guanine is nearly identical on the two surfaces, and heteroepitaxy appears to be the growth mechanism in both cases. Although the resolution of molecular details is superior for the graphite substrate, the simpler results on MoS2 are not only easier to interpret but also facilitate the understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 9 publications
8
95
1
Order By: Relevance
“…[20] In the recent years, a number of groups have carried out studies on how different nucleobases and nucleobase pairs self-assemble on a surface. [21,[31][32][33] The molecular self-assembly involving adsorption of nucleic acid bases on a graphite surface has been characterized by different spectroscopic techniques. The nucleobases self-assemble to form monolayers that are stabilized by hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[20] In the recent years, a number of groups have carried out studies on how different nucleobases and nucleobase pairs self-assemble on a surface. [21,[31][32][33] The molecular self-assembly involving adsorption of nucleic acid bases on a graphite surface has been characterized by different spectroscopic techniques. The nucleobases self-assemble to form monolayers that are stabilized by hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The purine and pyrimidine bases adsorb spontaneously from aqueous media onto inorganic solids and have been observed on the surfaces of graphite (17)(18)(19)(20)(21), MoS 2 (15,(18)(19)(20)(21), crystalline gold (22), and clays (23,24). Scanning probe microscopy (SPM) studies have shown that the bases are planar-arranged on these surfaces like jigsaw puzzle pieces.…”
mentioning
confidence: 99%
“…Scanning probe microscopy (SPM) studies have shown that the bases are planar-arranged on these surfaces like jigsaw puzzle pieces. They are stabilized by van der Waals interactions with the underlying surface and by hydrogen bonds between adjacent molecules (15,(18)(19)(20)(21)25), a configuration originally postulated on the basis of thermodynamic measurements made at the mercury-water interface (26). The hydrogen bonds between the bases are drawn from a discrete set of possible interactions including those of Watson-Crick pairing found in nucleic acids (15).…”
mentioning
confidence: 99%
“…For example, in the report of Maddocks et al [21], guanine, one of the four DNA bases, was observed, by using scanning tunneling microscopy (STM), to form a stable two-dimensional ordered array. These results are of crucial importance, as they support the hypothesis that the van der Waals interaction between MoS 2 and the DNA in the origami is of sufficient strength to destabilize the hydrogen bonds as well as the π-π stacking interactions in the relatively short duplex regions within the DNA origami constructs.…”
Section: Resultsmentioning
confidence: 99%